STUDY OF HEAT AND ENERGY PARAMETERS OF A VAPORCOMPRESSION HEAT PUMP - Uzakov, Gulom; Elmurodov, Nuriddin (Innovatsion texnologiyalar, 2024)
In this research work, the energy efficiency of the introduction of heat pumps into the energy supply systems of buildings in the conditions of Karshi city was evaluated based on the thermodynamic cycle of the heat pump operating on the basis of a low-temperature source and the experimental research of its parameters. During the experiments, the energy efficiency of the heat pump was determined at four temperatures 5 oC, 10 oC, 15 oC and 20 oC of the low-temperature source. R134a freon, safe for ozone, was used as the working fluid. It was observed that the energy conversion coefficient of the heat pump increases with the increase in the temperature of the low-temperature heat source. During the research, it was found that the value of the energy conversion coefficient of the heat pump at different temperatures of the low-temperature source changed from 2.1 to 3.5. Also, an energy conversion coefficient of 3.5 was achieved when a heat source with a temperature of 20 oC was used. Based on the results of the conducted experiment, it shows that the use of the heat pump in the heat supply systems is an effective solution, as the value of the energy conversion coefficient of the heat pump is greater than 2 at different temperatures of the low-temperature source in the conditions of Karshi city.